Adolescent Knowledge of Anemia and Iron Supplement Consumption Before and After Health Education - Mitra (GoAcademica Research & Publishing, 2020)
The purpose of this study was to describe adolescent knowledge of iron supplement anemia and consumption before and after health education. This research was quantitative with a quasi-experimental design using pre-posttest without control. The material presented in the form of lectures and videos on 119 students at 16 senior high school in Pekanbaru. Pre and Post-test to evaluate the level of knowledge of adolescents. The results showed that before counseling 35.5% of adolescents had never consumed iron supplements. After the intervention, the increase in correct answers ranged from 0.8 to 21.9 percent, with the highest rating being on vitamins that help with iron absorption, beverages that inhibit iron absorption and cause anemia. The average score for adolescent knowledge before intervention is 6.46. The average score after intervention increased to 7.27. T-Test results showed significant differences in knowledge scores before and after the intervention. Teenage Health Care Services need to be established as adolescent health counselors so that they can motivate other students in adolescent reproductive health, especially in consuming iron supplements.